1994
DOI: 10.1128/iai.62.5.1805-1812.1994
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Streptococcus mutans SR protein to human monocytes: production of tumor necrosis factor, interleukin 1, and interleukin 6

Abstract: To examine the possible implication of protein SR, an VII-related antigen from Streptococcus mutans OMZ 175 (serotype f), in inflammatory reactions, we tested the immunomodulatory effects of protein SR on human monocytes. Using biotinylated protein, we provide evidence that protein SR binds to human monocytes in dose-, time-, and calcium-dependent manners through specific interactions. These results were confirmed by competition experiments using either soluble human monocyte extract or anti-SR immunoglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…2). These results are similar to other reports showing that S. mutans stimulates the production of TNF-a and IL-1b in human peripheral blood mononuclear cells or human monocytes, or the S. mutans OMZ175 protein I/II induces the production of TNF-a and IL-1b in human synoviocytes (Benabdelmoumene et al, 1991;Soell et al, 1994;Jiang et al, 1999;Gourieux et al, 2001). Nuclear factor-jB is a multiunit transcription factor that plays a key role in the induction of genes for proinflammatory cytokines (Collart et al, 1990;Ziegler-Heitbrock et al, 1993;Neff et al, 2001) as well as many other immunoregulatory genes (Baeuerle, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…2). These results are similar to other reports showing that S. mutans stimulates the production of TNF-a and IL-1b in human peripheral blood mononuclear cells or human monocytes, or the S. mutans OMZ175 protein I/II induces the production of TNF-a and IL-1b in human synoviocytes (Benabdelmoumene et al, 1991;Soell et al, 1994;Jiang et al, 1999;Gourieux et al, 2001). Nuclear factor-jB is a multiunit transcription factor that plays a key role in the induction of genes for proinflammatory cytokines (Collart et al, 1990;Ziegler-Heitbrock et al, 1993;Neff et al, 2001) as well as many other immunoregulatory genes (Baeuerle, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Most species of oral streptococci express on their cell surface a high-molecular-mass polypeptide of the I/II family, which is a multifunctional adhesin with multiple ligand binding sites. This protein binds chiefly to salivary constituents such as salivary glycoproteins (Crowley et al, 1993) either in the fluid phase or adsorbed to hydroxyapatite, to human epithelial, endothelial and monocytic cells, and binding to cells occurs via lectin interactions specific for N-acetyl neuraminic acid and fucose (Soell et al, 1994;Vernier et al, 1996). Moreover, we and others (Love et al, 1997;Sciotti et al, 1997) have demonstrated the capacity of protein I/II to bind to extracellular and matrix proteins such as collagen I, laminin and fibronectin, which suggests the propensity of the bacteria or bacterial components to disseminate and persist in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…There is now evidence that protein I/IIf is involved in the adhesion of oral viridans streptococci to salivary glycoproteins, either in the¯uid phase or adsorbed to hydroxyapatite (Demuth et al, 1989;Lee et al, 1989;Brady et al, 1992;Munro et al, 1993;Moisset et al, 1994), and that protein I/IIf plays a role in virulence by interacting speci®cally with¯uid phase salivary agglutinins to mediate bacterial aggregation (Demuth et al, 1996;Kuykindoll and Holt, 1996;Crowley et al, 1999). Moreover, we and others have demonstrated the capacity of protein I/IIf to bind to extracellular matrix proteins, such as ®bronectin, collagen I and laminin (Love et al, 1997;Sciotti et al, 1997), and to epithelial, endothelial and monocytic cells (Soell et al, 1994;Vernier et al, 1996). We demonstrated recently that the speci®c binding of protein I/IIf from Streptococcus mutans serotype f to monocytic THP-1 cells occurs via lectin interactions spec-i®c for N-acetyl neuraminic acid (NANA) and fucose and is controlled by the extended V-region (Chatenay-Rivauday et al, 1998).…”
Section: Introductionmentioning
confidence: 72%
“…We demonstrated recently that the speci®c binding of protein I/IIf from Streptococcus mutans serotype f to monocytic THP-1 cells occurs via lectin interactions spec-i®c for N-acetyl neuraminic acid (NANA) and fucose and is controlled by the extended V-region (Chatenay-Rivauday et al, 1998). We also showed that (i) the binding of members of the oral viridans streptococci to cells induces the release of pro-in¯ammatory cytokines by epithelial and endothelial cells (Vernier et al, 1996); (ii) protein I/IIf belongs to the recently de®ned class of modulins and exerts immunomodulatory effects on human cells (Soell et al, 1994;Vernier et al, 1996). After binding to its cognate receptor, protein I/IIf promotes the induction of IL-8 from epithelial cells, IL-8 and IL-6 from endothelial cells, IL-1b, tumour necrosis factor alpha (TNF-a) and IL-6 from monocytes and the upregulation of E-selectin, ICAM-1 and VCAM-1 expression on endothelial cells (Vernier-Georgenthum et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation